Open at the close : literary essays on Harry Potter - Farr, Cecilia Konchar, 1958- (University Press of Mississippi, 2022)
"Contributions by Lauren R. Carmacci, Keridiana Chez, Kate Glassman, John Granger, Marie Schilling Grogan, Beatrice Groves, Tolonda Henderson, Nusaiba Imady, Cecilia Konchar Farr, Juliana Valadão Lopes, Amy Mars, Christina Phillips-Mattson, Patrick McCauley, Jennifer M. Reeher, Jonathan A. Rose, and Emily Strand Despite their decades-long, phenomenal success, the Harry Potter novels have attracted relatively little attention from literary critics and scholars. While popular books, articles, blogs, and fan sites for general readers proliferate, and while philosophers, historians, theologians, sociologists, psychologists, and even business professors have taken on book-length studies and edited essay collections about Harry Potter, literature scholars, outside of the children's books community, have paid few serious visits to the Potterverse. Could it be that scholars are still reluctant to recognize popular novels, especially those with genre labels "children's literature" or "fantasy," as worthy subjects for academic study? This book challenges that oversight, assembling and foregrounding some of the best literary critical work by scholars trying to move the needle on these novels to reflect their importance to twenty-first-century literate culture. In Open at the Close, contributors consciously address Harry Potter primarily as a literary phenomenon rather than a cultural one. They interrogate the novels on many levels, from multiple perspectives, and with various conclusions, but they come together around the overarching question: What is it about these books? At their heart, what is it that makes the Harry Potter novels so exceptionally compelling, so irresistible to their readers, and so relevant in our time?"--